2017
DOI: 10.1016/j.carj.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Compression of the Anterior Optic Pathway: A Rare Occurrence?

Abstract: Vascular compression of the ON and OC may not be an infrequent occurrence in the cranial cavity. Progressive and unexplainable visual impairment might possibly be caused by vascular-compressive neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It usually results in a slow progressive and painless structural and functional deterioration of optic nerve. The etiologic compressive masses can be varied in terms of different pathologic tissues, sizes, growth rates, biological behaviors, and systemic disturbances 1,2. Also, the retinotopic rearrangement of axonal fibers themselves at the site of compression can be region-specific along the pathway from intraocular, intraorbital, intracanalicular, intracranial parts of the optic nerve, chiasm, optic tract before synapse at the lateral geniculate body.…”
Section: Introductionmentioning
confidence: 99%
“…It usually results in a slow progressive and painless structural and functional deterioration of optic nerve. The etiologic compressive masses can be varied in terms of different pathologic tissues, sizes, growth rates, biological behaviors, and systemic disturbances 1,2. Also, the retinotopic rearrangement of axonal fibers themselves at the site of compression can be region-specific along the pathway from intraocular, intraorbital, intracanalicular, intracranial parts of the optic nerve, chiasm, optic tract before synapse at the lateral geniculate body.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Tsutumi et al of 183 patients suggested an 11% incidence while the previous study by Jacobson et al of 100 patients suggested a 17% incidence. 37,38 This would suggest other aetiologies of visual dysfunction must be excluded before interventions to alleviate vascular compression are considered. However, patients in the Tsutumi et al radiological study did not undergo full visual testing, so it is possible that patients had unidentified visual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients in the Tsutumi et al radiological study did not undergo full visual testing, so it is possible that patients had unidentified visual dysfunction. 37 This feature also highlights that there is an incomplete understanding of the exact mechanism of loss of function in artery-nerve compression and interaction. As yet unidentified factors may be involved in leading AVP compression to manifest with symptomatic visual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These aneurysms are difficult to diagnose since they are manifested only by a gradual decrease in visual acuity and the development of CS. Aneurysm rupture resulting in subarachnoid hemorrhage may be clinically manifested by sudden headache, neurological deficit and decrease in visual acuity [20,29,30].…”
Section: Intrachiasmal Lesionsmentioning
confidence: 99%